2021
DOI: 10.3390/cells11010008
|View full text |Cite
|
Sign up to set email alerts
|

Crimean–Congo Hemorrhagic Fever Virus Past Infections Are Associated with Two Innate Immune Response Candidate Genes in Dromedaries

Abstract: Dromedaries are an important livestock, used as beasts of burden and for meat and milk production. However, they can act as an intermediate source or vector for transmitting zoonotic viruses to humans, such as the Middle East respiratory syndrome coronavirus (MERS-CoV) or Crimean–Congo hemorrhagic fever virus (CCHFV). After several outbreaks of CCHFV in the Arabian Peninsula, recent studies have demonstrated that CCHFV is endemic in dromedaries and camel ticks in the United Arab Emirates (UAE). There is no app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Humans are the only known hosts that develop sickness following CCHFV infection, owing to the virus's asymptomatic presence in animal reservoirs, which allows it to circulate undetected [ 179 ]. Humans can become infected with CCHFV through tick bites or contact with contaminated animal tissues during and immediately after slaughter [ 180 , 181 ]. Notably, humans who had high CCHF seropositivity had a history of animal contact, animal husbandry, farming, and tick bites [ 182 ].…”
Section: Resultsmentioning
confidence: 99%
“…Humans are the only known hosts that develop sickness following CCHFV infection, owing to the virus's asymptomatic presence in animal reservoirs, which allows it to circulate undetected [ 179 ]. Humans can become infected with CCHFV through tick bites or contact with contaminated animal tissues during and immediately after slaughter [ 180 , 181 ]. Notably, humans who had high CCHF seropositivity had a history of animal contact, animal husbandry, farming, and tick bites [ 182 ].…”
Section: Resultsmentioning
confidence: 99%
“…We assumed there was a high possibility to find MERS-CoV or CCHFV in the sampled rodents and ticks because dromedary camels were kept nearby that were mainly used for tourism purposes. By concurrent sampling of these camels, we found CCHFV- as well as MERS-CoV-reactive antibodies in almost all of them [ 7 , 47 , 48 ]. CCHFV is a tick-borne virus, primarily maintained in ticks of the Hyalomma genus, and several mammalian livestock species act as amplifying hosts [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lado et al identified two candidate genes belonging to the innate immune system: FCAR and CLEC2B. The CLEC2B gene was associated with NK cell and stimulated natural killer cells to play an immune defense mechanism [ 27 ]. Mace and Orange demonstrated for the first time that CORO1A promoted NK cells to exert cytotoxic functions and immune secretion by regulating F-actin breakdown, thus exerting the function of lytic immune effectors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%